Cone-beam computed tomographic evaluation of accessory mental foramen in a Turkish population - Aytugar, Emre; Ozeren, Ceren; Lacin, Nihat; Veli, Ilknur; Cene, Erhan (SPRINGER, 2019)
PurposeThe aim of this study was to evaluate the frequency and location of accessory mental foramen (AMF) in a Turkish population using cone beam computerized tomography (CBCT).MethodCBCT images of 1005 patients were retrospectively reviewed from the archive of the Department of Oral and Maxillofacial Radiology, Faculty of Dentistry, Izmir Katip Celebi University. The prevalence, size, and localization of AMFs were assessed according to gender and age. In addition, the vertical and horizontal dimension of the mental foramen (MF) with and without AMF was measured to investigate the relationship between MF dimensions and the presence and absence of AMF. The average distance between the MF and AMF was also calculated. All measurements were then analyzed statistically.ResultsA total of 149 AMFs in 123 (12.23%) patients were identified on the CBCT images of the 1005 patients reviewed. There was no significant correlation between presence of AMF and gender (p =0.152). The most common localization of an AMF with respect to the MF was posterio-inferior (n=52; 34.89%). A statistically significant difference was also found between the vertical and horizontal dimensions of the MF with and without AMF (p <0.05).ConclusionThe results of this study demonstrate the high prevalence of AMF in the studied Turkish population. Considering the high prevalence and the structures passing through it, recognition of AMF and its detection using CBCT is important to prevent complications that may occur during and after surgical procedures.
Keywords: Accessory mental foramen; Mandible; Cone-beam computed tomography; Anatomy & Morphology